Varroa destructor infestation impairs the improvement of landing performance in foraging honeybees. Issue 9 (9th September 2020) - Muijres, Florian T.; van Dooremalen, Coby; Lankheet, Martin; Lugt, Heleen; de Vries, Lana J.; Van Langevelde, Frank
Abstract : The parasitic mite Varroa destructor is an important contributor to the high losses of western honeybees. Forager bees from Varroa -infested colonies show reduced homing and flight capacity; it is not known whether flight manoeuvrability and related learning capability are also affected. Here, we test how honeybees from Varroa -infested and control colonies fly in an environment that is unfamiliar at the beginning of each experimental day. Using stereoscopic high-speed videography, we analysed 555 landing manoeuvres recorded during 12 days of approximately 5 h in length. From this, we quantified landing success as percentage of successful landings, and assessed how this changed over time. We found that the forager workforce of Varroa -infested colonies did not improve their landing success over time, while for control bees landing success improved with approximately 10% each hour. Analysis of the landing trajectories showed that control bees improved landing success by increasing the ratio between in-flight aerodynamic braking and braking at impact on the landing platform; bees from Varroa -infested colonies did not increase this ratio over time. The Varroa -induced detriment to this landing skill-learning capability might limit forager bees from Varroa -infested colonies to adapt to new or challenging conditions; this might consequently contribute to Varroa -induced mortality of honeybee colonies.